2017
DOI: 10.1007/s00381-017-3346-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and insulin-like growth factor-1 in children with spastic cerebral palsy

Abstract: Both BMD and IGF-1 were significantly in low children with spastic CP; IGF-1 negatively correlates with the severity of osteopenia in children with spastic. Children with CP who are not independently ambulant or with severe GMFCS level or who use anticonvulsive drugs are at a high risk for developing low BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although we previously showed evidence supporting cognitive impairment in individuals with CP that is comparable to those observed in the older adult population with MCI ( 2 ), biological determinants of cognitive decline in adults with CP are still in scarcity ( 2 , 25 ). Despite a previous study examining the roles of circulating IGF-1 in bone mineral density in young adults with CP ( 19 , 26 ), no studies have associated circulating IGF-1 with cognition in adults with CP. Whether circulating IGF-1 is a biological determinant of cognitive aging in adults with CP is thus unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Although we previously showed evidence supporting cognitive impairment in individuals with CP that is comparable to those observed in the older adult population with MCI ( 2 ), biological determinants of cognitive decline in adults with CP are still in scarcity ( 2 , 25 ). Despite a previous study examining the roles of circulating IGF-1 in bone mineral density in young adults with CP ( 19 , 26 ), no studies have associated circulating IGF-1 with cognition in adults with CP. Whether circulating IGF-1 is a biological determinant of cognitive aging in adults with CP is thus unknown.…”
Section: Introductionmentioning
confidence: 94%
“…BMD was significantly decreased in children with spastic CP compared to healthy children and was associated with low circulating IGF-1 levels, severe GMFCS level, and use of anticonvulsive drugs. Children with CP also exhibited increased fracture risk (Nazif et al, 2017).…”
Section: Cerebral Palsymentioning
confidence: 99%
“…Although a recent review compares the scientific works about the interaction between vitamin D and GH disorders (mainly GHD and acromegaly) on populations of adults and children [6571], there is currently no review that has collected together the clinical works that compare more generally vitamin D and the GH/IGF axis. A PubMed research for MEDLINE filtered for pediatric age (0–18 year-old subjects) was undertaken by using the following terms as key words: “Vitamin D” and “Growth”, “Growth Hormone” or “GH”, “Insulin-like Growth Factor-1” or “IGF-1”, and “Growth Hormone Deficiency” or “GHD”.…”
Section: Vitamin D Metabolism and Gh In Clinical Pediatric Studiesmentioning
confidence: 99%
“…Among these two biochemical parameters, the authors also found a direct correlation that strengthens the idea of an IGF-1/vitamin D axis with mutual influences. This could also explain the osteopenia that characterizes patients with CP [71].…”
Section: Vitamin D Metabolism and Gh In Clinical Pediatric Studiesmentioning
confidence: 99%